2009
DOI: 10.1111/j.1743-6109.2009.01273.x
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Coerced Anal Sex and Psychopathology, Marital Distress and Non-Sexual Violence

Abstract: Background There is a dearth of scientific data on anal intercourse in heterosexual relationships. Likewise, anal sex within marital relationships has yet to be fully explored. Objectives Among a representative sample of married women in the Iranian capital, Tehran, we aimed to determine the association of self-reported coerced anal sex with: (i) self-reported coerced vaginal sex; (ii) self-reported non-sexual violence; (iii)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…As found in this study, a vaginal penetration without condom is almost the rule during rape [6] [12] than it is in male victims and in marital sexual assault [13] [14].…”
Section: Discussionmentioning
confidence: 89%
“…As found in this study, a vaginal penetration without condom is almost the rule during rape [6] [12] than it is in male victims and in marital sexual assault [13] [14].…”
Section: Discussionmentioning
confidence: 89%
“…As we described elsewhere [17], the interviewers were trained to administer a structured interview lasting between 1:00 and 1:15 hours for data collection on cultural issues. The male and female subjects were interviewed separately.…”
Section: Methodsmentioning
confidence: 99%
“…De Visser et al [ 8 , 9 ] explained that the impact of sexual IPV goes beyond sexual function and includes psychosocial distress, substance use, anxiety, depression, and suicide. Women who have experienced sexual IPV are also at risk for mental health issues and relationship problems [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Victims of other types of violence (e.g., physical and psychological) are more likely to experience sexual IPV [ 19 ]. The explanation for this relationship is that sexual, psychological, and physical aggression tend to co-occur [ 10 ]. A study examining a community sample reported that 95% of women with a history of physical violence, compared to only 41% of women without such history, have been subjected to sexual IPV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation